2018
DOI: 10.1038/s41598-018-34353-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of measurement noise, experimental design, and estimation methods on Modular Response Analysis based network reconstruction

Abstract: Modular Response Analysis (MRA) is a method to reconstruct signalling networks from steady-state perturbation data which has frequently been used in different settings. Since these data are usually noisy due to multi-step measurement procedures and biological variability, it is important to investigate the effect of this noise onto network reconstruction. Here we present a systematic study to investigate propagation of noise from concentration measurements to network structures. Therefore, we design an in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 22 publications
2
41
1
Order By: Relevance
“…Lastly, one million matrices were generated sampling normal distributions, one distribution for each with mean equal to the average of the 6 raw data replicates and specific variance obtained by SPC. Note that, in practice, different displayed very different variances in some cases on the contrary to Thomaseth et al study 27 . The 95% CIs were obtained from the 2.5th and 97.5th percentiles.…”
Section: Methodscontrasting
confidence: 62%
See 1 more Smart Citation
“…Lastly, one million matrices were generated sampling normal distributions, one distribution for each with mean equal to the average of the 6 raw data replicates and specific variance obtained by SPC. Note that, in practice, different displayed very different variances in some cases on the contrary to Thomaseth et al study 27 . The 95% CIs were obtained from the 2.5th and 97.5th percentiles.…”
Section: Methodscontrasting
confidence: 62%
“…SPC can be used for normally distributed data, which will be the case here, but also in a nonparametric manner. In addition to SPC, our bootstrap procedure was also influenced by recent results discussing the propagation of noise in the data across MRA calculations 27 . These results showed that CI estimations on MRA parameters are best obtained by considering the noise on global response coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…The local responses ðr Xj XjÀ1 , r X1T Þ are also referred to as connection coefficients, because they quantify the strengths of direct connections between network nodes (Bastiaens et al, 2015;Kholodenko, 2007;Thomaseth et al, 2018). The connection coefficients r XjXjÀ1 are positive because each kinase is activated by its immediately preceding kinase.…”
Section: Can Feedback Circuitry Reactivate Signaling?mentioning
confidence: 99%
“…For example, the observed impairment of the p53 response in response to the JNK inhibitor could be due to a direct JNK-p53 interaction or an indirect JNK-p38-p53 interaction loop. To detangle direct from indirect effects, formal network reconstruction techniques have to be applied 2428 . Here, we use the constructed model and parameter estimation to identify the interactions parameters.…”
Section: Resultsmentioning
confidence: 99%